Analysis of a High-Dimensional Extended B92 Protocol - Iqbal, Hasan; Krawec, Walter O. (Quantum information processing, 2021)
Quantum key distribution (QKD) allows two parties to establish a shared secret key that is secure against adversaries with unlimited computational power. One such protocol named B92 is quite appealing due to its simplicity but is highly sensitive to channel noise. In this work, we investigate a high-dimensional variant of an extended version of the B92 protocol and show that it can distill a key over high noise channels. The protocol we consider requires that Alice sends only three high-dimensional states and Bob only performs partial measurements. We perform an information-theoretic security analysis of our protocol and compare its key rate to that of a high-dimensional BB84 protocol over depolarization and amplitude damping channels.